Manajemen Perubahan Melalui Perencanaan Proyek: Strategi Pengendalian Efektif di Lembaga Pendidikan - Refnawati, Refnawati; Yovica, Alia; Octavia, Lidya Fransiska; Fazis, M. (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to understand change management through project planning as an effective control strategy in educational institutions. This study uses a literature review approach as the main method. Data sources are obtained from various scholarly articles, academic books, proceedings, and policy documents. The databases used include Google Scholar, with search keywords such as "change management in education", "project planning in educational institutions", "educational reform strategies", and "project-based change control". The analysis is conducted qualitatively with a thematic approach. The results of the data analysis indicate that the systematics of the planning process follows the following sequence: determining objectives, identifying targets, assessing the current position against objectives, selecting alternatives, and arranging a series of steps to achieve the objectives. Strategic planning includes decisions that have significant implications for project implementation, such as design philosophy, determining the weight of key targets, selecting the type of contract, using a third-party organization to handle implementation, and others